Participation of Community Leaders in Community Development Activities at the Sawla-Tuna-Kalb District of the Northern Region - Addae, D. (University of Ghana, 2010)
The invaluable role played by community leaders in any development activity cannot be overemphasized. This is because through the participation of community leaders in development activities, community members could also be influenced to participate. The study therefore, identified the extent to which community leaders participate in development activities in the Sawla-Tuna-Kalba district. Related literature was reviewed on the concept of leadership, leaders and group effectiveness, community development, leaders’ participation in community development, among others. The population of the study consisted of all community leaders at Sawla-Tuna-Kalba district of the Northern Region. This included chiefs and elders, unit committee members, opinion leaders, leaders of women groups, and youth leaders. One hundred community leaders formed the sample for the study. The study used a descriptive survey design. Data was gathered from the respondents with the help of an interview schedule. The data was analysed using the SPSS software. The following were the major results of the study: • The leaders identified educational, constructional, sanitation, and environmental activities as community development activities that were undertaken in the district from 2007-2009. • Majority of the community leaders participated in varying levels of planning community development activities in the district. On the contrary, majority of the community leaders did not participate in implementing, and monitoring and evaluation of community development activities in the district. • Promotion of peace and stability in the district, provision of rewards to leaders, and availability of funds for development activities were some of things indicated by community as ways by which their participation in community development activities could be enhanced. Some of the major findings of the study were that: • Constructional, educational, sanitation, and environmental activities were the various categories of community development activities undertaken in the district within the past two years. • Majority of the community leaders participate in varying levels of the planning of development activities. • Community leaders were of the view that providing them with rewards, involving community members in development activities, promoting peace and harmony among the various groups in the district, and organizing training programmes for them, were some of the ways of enhancing their participation in development activities in the district. The study recommended amongst others that avenues should be created for leaders to continuously participate in the planning, implementing, and monitoring and evaluation of community development activities since such the participation of leaders in those stages were crucial to the success of development activities.
Thesis(M.Phil)-University of Ghana, 2010
Keywords: Communities Leaders; Community Development; Development Activities